PENGARUH KOMPOS KOTORAN KAMBING TERHADAP KANDUNGAN KARBON DAN FOSFOR TANAH DARI KEBUN KOPI BANGELAN - Radifta Adika Suarmaprasetya; S Soemarno (Jurnal Tanah dan Sumberdaya Lahan, 2021)
Inceptisol has a special characteristic, which is low in organic matter. Other chemical problems possessed by Inceptisol include acidic pH, high clay content, and washable surface layers. The compost of goat manure can improve soil chemical properties. The purpose of this study was to determine the effect of the application of goat manure compost at various doses on the carbon and phosphorus content of Inceptisol soil in Bangelan, Malang, East Java. The treatments tested were K1D1 (0-20 cm depth, without compost dose), K1D2 (0-20 cm depth, with compost dose 0.5 g 500 g-1 soil), K1D3 (0-20 depth, with compost dose 1 g 500 g-1 soil), K2D1 (20-40 cm depth, without compost dose), K2D2 (20-40 cm depth, with compost dose 0.5 g 500 g-1 soil), K2D3 (20-40cm depth, with compost dose 1 g 500 g-1 soil), K3D1 (40-60 cm depth, without compost dose), K3D2 (40-60 cm depth, with compost dose 0.5 g 500 g-1 soil), K3D3 (40-60 cm depth, with compost dose 1 g 500 g-1 of soil). The nine treatments were arranged in a completely randomized factorial design with three replications. The results showed that at a depth of 0-20 cm, 20-40 cm, and 40-60 cm with an additional dose of 1 g 500 g-1 of soil was the best dose given into the soil because it had a significant effect on increasing pH, C-organic, available P and total P in the soil.